2020
DOI: 10.4085/1062-6050-123-19
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Performance of High School Rugby Players on the Sport Concussion Assessment Tool 5

Abstract: Context: Version 5 of the Sport Concussion Assessment Tool (SCAT5) was released in 2017 with an additional 10-word list option in the memory section and additional instructions for completing the symptom scale.Objective: To provide reference scores for high school rugby union players on the SCAT5, including immediate memory using the 10-word list, and examine how age, sex, and concussion history affected performance.Design: Cross-sectional study. Setting: Calgary, Alberta high schools.Patients or Other Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
(35 reference statements)
5
24
1
Order By: Relevance
“…Chronic mTBI patients completed the NSI symptom questionnaire, which is widely used in assessment of mTBI symptoms [23,44]. The NSI and subscales [45] have acceptable reliability in characterising presence and tracking severity of symptoms in TBI [45,46]. Therefore, the NSI is widely used in clinical practice and remains the cornerstone of clinical symptom assessment and supports the use as reference in this study.…”
Section: Self-reported Symptomssupporting
confidence: 57%
“…Chronic mTBI patients completed the NSI symptom questionnaire, which is widely used in assessment of mTBI symptoms [23,44]. The NSI and subscales [45] have acceptable reliability in characterising presence and tracking severity of symptoms in TBI [45,46]. Therefore, the NSI is widely used in clinical practice and remains the cornerstone of clinical symptom assessment and supports the use as reference in this study.…”
Section: Self-reported Symptomssupporting
confidence: 57%
“…A sample of high school rugby players obtained a median total score on Immediate Memory of 23 for men and 21 for women, and scores of 7 in Delayed Recall and 3 in Digits Backward for the combined sample. 30 A large sample of rugby union athletes achieved an average of 21.5 (SD=3.7; median=21) on Immediate Memory and 7.1 (SD=1.9; median=7) on Delayed Recall. 31 All of these studies determined that the ten-word list largely eliminated the ceiling effects found on the five-word lists.…”
Section: Discussionmentioning
confidence: 98%
“…16 It is possible that performance in these domains experiences a ceiling effect and therefore scaling and multimodal testing is vital. 5,17 These domains of the SCAT may have lower clinical utility for concussion diagnosis in cricket, particularly if considered independently, however further research is needed.…”
Section: Discussionmentioning
confidence: 99%